Improvement of Soil Chemical Properties of Typic Hapludult After Application of Organic and Inorganic Fertilizers - Mubarok, Syariful; Kusumiyati, Kusumiyati; Muhardiono, Iman; Yuniarti, Anni; Rosniawati, Santi; Suminar, Erni (UNIVERSITY OF LAMPUNG, 2017)
Tuberose (Polyanthes tuberosa L.) is a potential flowering plant that will be developed in Jatinangor, West Java, Indonesia. However, the characteristics of Typic Hapludult soil in Jatinangor , i.e. clay texture, acidic pH, and high amount of total-P but low in available-P cause the tuberose difficult to grow optimally. The aim of this study was to obtain the potential ratio of organic and inorganic fertilizer dosages for tuberose grown on Typic Hapludult. The combinations of organic and inorganic fertilizers with different ratios (0/0; 0/1; 1/0; 0.5/0.5; 0.5/1; 1/0.5; 1/1.5; 1.5/0; 1.5/0.5, and 1.5/) were applied. The application of the combination of organic and inorganic fertilizers showed positive effects on soil pH, available-P, total-P, and fresh weight of tuberose grown on Typic Hapludult. The application of 50% organic fertilizer + 50% inorganic fertilizer was an effective combination that was able to increase the fresh weight of tuberose up to 9240 g plant-1 or increasing the fresh weight by 39% in comparison to that in the control treatment (without fertilizer application).Â